Study of a Novel APAP Algorithm for the Treatment of Obstructive Sleep Apnea in Women. Issue 11 (1st November 2015) - McArdle, Nigel; King, Stuart; Shepherd, Kelly; Baker, Vanessa; Ramanan, Dinesh; Ketheeswaran, Sahisha; Bateman, Peter; Wimms, Alison; Armitstead, Jeff; Richards, Glenn; Hillman, David; Eastwood, Peter
Abstract: Study Objectives: To assess the efficacy of a novel female-specific autotitrating continuous positive airway pressure (CPAP) algorithm (AutoSet for her, AfH) in premenopausal women relative to a standard autotitrating algorithm (AutoSet, S9) (ResMed Ltd., Bella Vista, New South Wales, Australia). Design: Prospective randomised crossover noninferiority trial. Setting: Tertiary hospital sleep clinic and university research sleep laboratory. Participants: 20 female patients with obstructive sleep apnea (OSA) established on long-term CPAP treatment. Interventions: Treatment with 1 night each of AfH and AutoSet while monitored with overnight laboratory-based polysomnography (PSG); order randomly allocated. Measurements and Results: The primary outcome variables were the apnea-hypopnea index (AHI) and 3% oxygen desaturation index (ODI 3%) determined from PSG. Treatment efficacy on the AfH night was noninferior to the AutoSet night as assessed by median (IQR) AHI (1.2 [0.60–1.85]/h versus 1.15 [0.40–2.85]/h, respectively, P = 0.51) and 3% ODI (0.85 [0.25–1.5]/h versus 0.5 [0.25–2.55]/h, respectively, P = 0.83). Other PSG measures were similar, except for the percentage of the night spent in flow limitation, which was lower on the AfH (0.14%) than the AutoSet night (0.19%, P = 0.007). The device-downloaded 95th centile pressure on the AfH night was also lower than on the AutoSet night (10.6 ± 1.7 versus 11.6 ± 2.6 cmH2 O, respectively; mean difference [95% confidence interval]: −1.1 [−2.13 to −0.01] cm H2 O). Conclusion: Among premenopausal women a novel female-specific autotitrating algorithm (AfH) is as effective as the standard AutoSet algorithm in controlling obstructive sleep apnea (OSA). The new algorithm may reduce flow limitation more than the standard algorithm and achieve control of OSA at a lower (95th centile) pressure.